(3GdcTGa aj JaSjQ GdbQBf GdYXje hEYQGHgs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3ShQI GdCMRGH Yf bGd bGd di CHj Hf cYH ce YOO ShQI GdCMRGH bdJ UdGUGA SHYjf Bjg s
(3BNQgG (B:s
[ (3BNQ ShQI ZGaQ (B] (3bhdg (B: (3aEPG LGA GeQ Gddg bVi HGdMb Ci NSQhG hbJ eLF CeQ Gddg Ch hbJ GdbVGA HGdMb Yf QShd Gdgd Udi Gddg Ydjg hSd ef bQC ShQI GdeDef de jHb QhM fHi hdG UOjb hdGTgjO hdG eDef GdCUdi Ydjg hGSJZaQ dg Je GdLRA GdKGdK s
(3Ydjg JedcGJ CcedJ HNW eZQHis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1475s
Keywords: (3GddZIs